2018
DOI: 10.1212/nxi.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Pleocytosis is not fully responsible for low CSF glucose in meningitis

Abstract: Objective:The mechanism of hypoglycorrhachia—low CSF glucose—in meningitis remains unknown. We sought to evaluate the relative contribution of CSF inflammation vs microorganisms (bacteria and fungi) in lowering CSF glucose levels.Methods:We retrospectively categorized CSF profiles into microbial and aseptic meningitis and analyzed CSF leukocyte count, glucose, and protein concentrations. We assessed the relationship between these markers using multivariate and stratified linear regression analysis for initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
1
17
0
2
Order By: Relevance
“…Low CSF glucose level may be related to glucose utilization by microorganisms, and the degree of hypoglycemia is directly correlated with the inflammatory process [13]. A previous study speculated that the low CSF glucose level can be used as a marker for the diagnosis of microbial meningitis [14]. Our results showed that the CSF profile of AIDS-associated T. marneffei CNS infection is extremely similar to those of other types of fungal meningitis, especially cryptococcal meningitis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Low CSF glucose level may be related to glucose utilization by microorganisms, and the degree of hypoglycemia is directly correlated with the inflammatory process [13]. A previous study speculated that the low CSF glucose level can be used as a marker for the diagnosis of microbial meningitis [14]. Our results showed that the CSF profile of AIDS-associated T. marneffei CNS infection is extremely similar to those of other types of fungal meningitis, especially cryptococcal meningitis.…”
Section: Discussionsupporting
confidence: 51%
“…Among them, one had positive results in both blood culture and bone marrow culture, one had a positive result in blood culture, and one patient had a positive result in urine culture. The median duration of CSF culture for T. marneffei was 11.5 days (IQR [6][7][8][9][10][11][12][13][14]) ( Table 2).…”
Section: Csf Profiles and Routine Blood Testmentioning
confidence: 99%
“…Hypoglycorrhachia (low CSF glucose concentration) is a cardinal feature of bacterial meningitis. 16 CSF glucose concentration < 40 mg/dL or CSF-to-serum ratio < 0.40 is worrisome for bacterial meningitis. A normal CSF-to-serum glucose ratio is 0.6.…”
Section: Serum Biomarkers May Assist In the Diagnosis Of Bacterialmentioning
confidence: 99%
“…katabolisme glukosa oleh patogen. 10 Patogen juga akan memicu reaksi inflamasi sehingga terjadi kenaikan jumlah leukosit pada LCS. Perubahan komposisi ini memberikan efek perubahan warna dan mengeruhnya LCS sehingga analisis yang dapat dilakukan adalah tingkat perubahan dari tiap parameter tersebut.…”
unclassified
“…Karenanya, meskipun terjadi infeksi yang berat dan ekstensif kadar glukosa tidak menurun sebanyak patogen lain. 10 Hingga saat ini, masih belum ditemukan patofisiologi yang jelas mengenai perubahan spesifik dari tiap parameter LCS, seperti yang dilaporkan oleh Thuong. 13 Pemeriksaan LCS juga dipengaruhi oleh prosedur pengambilan sampel yang kurang tepat, kadar patogen itu sendiri, dan penggunaan antibiotik yang dapat mengakibatkan hasil pemeriksaan LCS mengalami perubahan atau tampak normal.…”
unclassified